Pengaruh Inflasi Indonesia Dan Bi Repo 7 Days Terhadap Kinerja Bank Devisa - Sinta Listari; Ricky Adi Pratama (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
This study aims to analyze the effect of inflation and BI 7-Day (Reverse) Repo Rate on Retrun On Assets(ROA). The data obtained were then entered into the Statistical Package Social Sciences (SPSS) program to carry out advanced statistical analysis. Data obtained from the financial statements of 10 banks listed on the Indonesia Stock Exchange (IDX) during the period 2015 to 2019. The analysis techniques used are classical assumption tests, hypothesis testing, and others. The results obtained from the simultaneous hypothesis test (f test) show that inflation and the BI 7-Day (Reverse) Repo Rate simultaneously have an effect on Retrun On Assets(ROA). The results of the partial test (t test) show that inflation data has a significant negative effect on Retrun On Assets(ROA) and BI 7-Day (Reverse) Repo Rate data has a significant positive effect on Retrun On Assets(ROA). The result of the coefficient of determination with adjusted R2 shows that the predictive ability of this research data is 98.8%, meaning that the independent variables, namely Inflation and BI 7-Day (Reverse) Repo Rate affect the dependent variable, namely Retrun On Assets(ROA). amounting to 98.8 % Keywords : Inflation BI 7-Day (Reverse) Repo Rate, Retrun On Assets(ROA)